Primary orbital melanoma: a case series and literature review. (3rd September 2018) - Figueira, Edwin; Rajak, Saul; McKelvie, Penny; Kalantzis, George; Ismail, Azzam; Gonzales, Michael; James, Craig; McNab, Alan; Selva, Dinesh
ABSTRACT: Primary orbital melanoma (POM) is a very rare condition. We report further four cases and review all previously reported cases. We present a multicentre retrospective review of patients with POM. Clinical, radiological, surgical, histological, and follow-up data is presented. Four patients with POM were identified between 2000 and 2013. All presented with proptosis and diplopia without reduced vision. Two had known pre-existing blue cell naevi. All were stage T1N0M0. All underwent exenteration with adjuvant radiotherapy. All are disease free at follow-up durations of 24–151 months. The present three cases and review of all cases in the literature suggest a higher likelihood of disease-free survival from primary exenteration (7/8 disease-free survival, 1/8 death from metastatic disease) than wide local excision (7/16 disease-free survival, 9 recurrence or metastasis of whom 4 died). Adjuvant radiotherapy may additionally improve outcomes.